H-2A Workers in Demand in the Ornamental Horticulture Industry : FE1141, 2/2024 - Wei, Xuan; Campbell, Benjamin L.; Khachatryan, Hayk; Brumfield, Robin G. (EDIS, 2024)
The US agricultural industry depends on immigrant farm labor, particularly in the specialty crop sector where tasks like harvesting require a lot of labor. Most US farmworkers are from other countries, and almost half are not authorized to work in the United States. The importance of immigrant labor in meeting the demand for workers in the nursery and floriculture production sector has been further highlighted with this industry's recent growth. This publication offers an overview of the increasing demand for H-2A workers in the ornamental horticulture industry, examines growers' challenges, and explores the underlying factors affecting workers’ participation in the H-2A program. It guides industry stakeholders to monitor changes in immigration policies and labor regulations, including the H-2A program and to adjust labor management practices accordingly. It includes strategies to address labor challenges and remain competitive in the marketplace